The Multiple Functions of the Nucleolus in Plant Development, Disease and Stress Responses - Kalinina, Natalia O.; Makarova, Svetlana; Makhotenko, Antonida; Love, Andrew J.; Taliansky, Michael (Frontiers in Plant Science, 2018)
The nucleolus is the most conspicuous domain in the eukaryotic cell nucleus, whose main function is ribosomal RNA (rRNA) synthesis and ribosome biogenesis. However, there is growing evidence that the nucleolus is also implicated in many other aspects of cell biology, such as regulation of cell cycle, growth and development, senescence, telomerase activity, gene silencing, responses to biotic and abiotic stresses. In the first part of the review, we briefly assess the traditional roles of the plant nucleolus in rRNA synthesis and ribosome biogenesis as well as possible functions in other RNA regulatory pathways such as splicing, nonsense-mediated mRNA decay and RNA silencing. In the second part of the review we summarize recent progress and discuss already known and new hypothetical roles of the nucleolus in plant growth and development. In addition, this part will highlight studies showing new nucleolar functions involved in responses to pathogen attack and abiotic stress. Cross-talk between the nucleolus and Cajal bodies is also discussed in the context of their association with poly(ADP ribose)polymerase (PARP), which is known to play a crucial role in various physiological processes including growth, development and responses to biotic and abiotic stresses.